1
$\begingroup$

Let:

$f:\mathbb{R}\rightarrow\mathbb{R}$ be differentiable.

$u:\mathbb{R}^2\rightarrow\mathbb{R}$ and $u(x,y)=e^{-y}f(x+y^2)$

Show that: $$2y\frac{\partial{u}}{\partial{x}}-\frac{\partial{u}}{\partial{y}}=u$$

My attempt has been to first work out the two partial derivatives and plug them in, however I am not very confident in my notation, for example:

$e^{-y}\frac{\partial{f(x+y^2)}}{\partial{y}}$ is the second part of my working of partial u/partial y, first * derivative of second

The next step is: $2ye^{-y}\frac{\partial{f(x+y^2)}}{\partial{y}}$ but that looks the same as before, my notation doesn't show f(x+y^2) and the partial derivative of f wrt a variable at a point as being different. How do I overcome this?

I've never been formally taught or had the need for the vertical bar notation, but I sense this is what the notation solves, how do I write it?

Addendum: I've not LaTeXed a lot of it, I find it a laggy choir at present, please don't take this as laziness, I'm also going to try introducing a new variable used for x+y^2 but on paper. If I answer it I shall report back, sorry for mixing up my mu and u, it's one of those prints of a scan of an old text-book, the toner is shiny on the cheap paper and it's black and white, not gray-scale a choir to read!

Addendum 2: Here, it works, but I'm not sure if it's errors canceling or not:

Let: $\lambda:\mathbb{R}^2\rightarrow\mathbb{R}$, $\lambda(x,y)=x+y^2$

Now:

$u(x,y) = e^{-y}f(\lambda)$ (I feel I need not write $\lambda(x,y)$ all the time)

$$\frac{\partial{u}}{\partial{x}}=e^{-y}\frac{df(\lambda)}{\partial{x}}=e^{-y}\frac{df}{d\lambda}.\frac{\partial{\lambda}}{\partial{x}}=e^{-y}\frac{df}{d\lambda}$$

and

$$\frac{\partial{u}}{\partial{y}}=e^{-y}\frac{df(\lambda)}{\partial{y}}+\frac{\partial}{\partial{y}}[e^{-y}]f(\lambda)$$ Now there I've written partial by partial-y, this is why I am not that happy with my notation.... but d/partial y doesn't look right either...

Anyway: $$\frac{\partial{u}}{\partial{y}}=-e^{-y}f(\lambda)+e^{-y}\frac{df}{d\lambda}.\frac{\partial{\lambda}}{\partial{y}}=e^{-y}[2y\frac{df}{d\lambda}-f(\lambda)]$$

To show that is just to bung those in.

$\endgroup$
  • 1
    $\begingroup$ Did you misplace $u$ instead of $\mu$? $\endgroup$ – Kaster Aug 29 '13 at 19:56
  • $\begingroup$ See addendum, I'll change it though as someone agrees with your comment $\endgroup$ – Alec Teal Aug 29 '13 at 19:59
  • $\begingroup$ @Kaster is $\frac{\partial{f(\lambda)}}{\partial{x}}=\frac{\partial{f}}{\partial{\lambda}}.\frac{\partial{\lambda}}{\partial{x}}$ allowed? Where $\lambda:\mathbb{R}^2\rightarrow\mathbb{R}$ and $\lambda(x,y)=x+y^2$ or is it a matter of errors canceling. It seems logical at least. But I'd prefer to write $\frac{df}{d\lambda}$ $\endgroup$ – Alec Teal Aug 29 '13 at 20:14
1
$\begingroup$

$$ \lambda (x,y) = x+y^2 \\ u = e^{-y}f(\lambda) \\ u_x = e^{-y} f'(\lambda) \lambda_x = e^{-y} f'(\lambda)\\ u_y = -e^{-y}f(\lambda) + e^{-y} f'(\lambda) \lambda_y = e^{-y} \left[2yf'(\lambda) -f(\lambda)\right ] \\ 2y u_x - u_y = 2y e^{-y} f'(\lambda) - 2ye^{-y}f'(\lambda) + e^{-y} f(\lambda) = e^{-y} f(\lambda) = u $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.